Pelatihan Pendidikan Karakter bagi Pelatih Pencak Silat Persaudaraan Setia Hati Terate “PSHT” Cabang Pamekasan - Fredy Yunanto; Ria Kasanova; Syaiful Syaiful; Mohammad Rudiyanto; Syaiful Anam; Hasbullah Hasbullah (Gapenas Publisher, 2022)
This training course aims to increase the knowledge of the pencak silat trainer of the Setia Hati Terate